Pesan Moral Dalam Visual Peringatan Darurat: Analisis Semiotika Charles Sanders Peirce - Rahmat Hidayat; Moehammad Gafar Yoedtadi (Koneksi, 2026)
Visual elements such as symbols or images are often used to evoke public emotions and convey moral messages through viral posts on social media. The viral post about the "Emergency Warning" with the Garuda symbol on a blue background is an interesting phenomenon to study, especially in the context of representation and the moral message contained therein. This shows that visualizations that are appropriate to the circumstances that occur around can strengthen the delivery of important information to the public. This study aims to uncover the moral message behind the Garuda symbol on a blue background with the words "Emergency Warning" using Charles Sanders Peirce's semiotic approach. This research method is qualitative with the analysis of signs, objects, and logistical interpretation based on Peirce's semiotic theory. The subject of the study is the visual symbol of Garuda on a blue background with the words "Emergency Warning," while the object of the research is the moral message contained therein. The results show that the color blue reflects stability, the Garuda symbol represents the values ​​of Pancasila, and the text "Emergency Warning" gives a sense of urgency. However, the visual noise in this image affects public understanding, resulting in diverse interpretations. This research emphasizes the importance of visual clarity in conveying moral messages in national symbols. Elemen visual seperti simbol atau gambar, sering digunakan untuk menggugah emosi masyarakat dan menyampaikan pesan moral melalui postingan viral di media sosial. Postingan viral tentang “Peringatan Darurat” dengan simbol Garuda berlatar biru menjadi fenomena menarik untuk dikaji, terutama dalam konteks representasi dan pesan moral yang terkandung di dalamnya. Hal ini menunjukkan bahwa visualisasi yang sesuai dengan keadaan yang terjadi di sekitar dapat memperkuat penyampaian informasi penting kepada publik. Penelitian ini bertujuan untuk mengungkap pesan moral di balik simbol Garuda berlatar biru dengan tulisan "Peringatan Darurat" yang menggunakan pendekatan semiotika Charles Sanders Peirce. Metode penelitian ini adalah kualitatif dengan analisis tanda, objek, dan interpretasi logis berdasarkan teori semiotika Peirce. Subjek penelitian adalah visual simbol Garuda berlatar biru dengan tulisan "Peringatan Darurat," sementara objek penelitian adalah pesan moral yang terkandung di dalamnya. Hasil penelitian menunjukkan bahwa warna biru mencerminkan kestabilan, simbol Garuda merepresentasikan nilai-nilai Pancasila, dan teks "Peringatan Darurat" memberikan kesan urgensi. Namun, noise visual pada gambar ini memengaruhi pemahaman publik, menghasilkan interpretasi yang beragam. Penelitian ini menegaskan pentingnya kejelasan visual dalam menyampaikan pesan moral pada simbol - simbol nasional.